2019
DOI: 10.1186/s13018-019-1107-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the AMADEUS score and preoperative clinical patient-reported outcome measurements (PROMs) in patients undergoing matrix-induced autologous chondrocyte implantation (MACI)

Abstract: BackgroundRecently, the AMADEUS (Area Measurement And DEpth Underlying Structures) grading system has been introduced to evaluate and grade osteochondral lesions prior to cartilage surgery. The AMADEUS score has not been connected to clinical data in order to test a potential clincial impact.PurposeTo examine the correlation between the AMADEUS score and preoperative patient-reported outcome measurements (PROMs).Study designCase seriesMethodsPatients treated with matrix-induced autologous chondrocyte implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…By implementing the subscores “cartilage defect size”, “defect depth” and “subchondral bone involvement”, the AMADEUS is thought to accurately portray defect severity and to aid in clinical decision-making regarding cartilage repair surgery. The AMADEUS score has already been linked to clinical data demonstrating moderate correlation with patient reported outcomes measures (PROMs) [ 24 ]. However, its association with arthroscopic chondral defect grading systems has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…By implementing the subscores “cartilage defect size”, “defect depth” and “subchondral bone involvement”, the AMADEUS is thought to accurately portray defect severity and to aid in clinical decision-making regarding cartilage repair surgery. The AMADEUS score has already been linked to clinical data demonstrating moderate correlation with patient reported outcomes measures (PROMs) [ 24 ]. However, its association with arthroscopic chondral defect grading systems has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…For the preoperative morphologic assessment, the semiquantitative AMADEUS score was obtained as previously described. 27,48 The total AMADEUS score ranged from 100 (no osteochondral defect) to 0 (severe defect). Based on the total AMADEUS score, an AMADEUS grade was assigned to each patient: grade I, score >75; grade II, score >50 and ≤75; grade III, score >25 and ≤50; and grade IV, score ≤25.…”
Section: Methodsmentioning
confidence: 99%
“…Pati et al derived cartilage dECM bioinks from porcine cartilage and showed that the cartilage dECM bioink induced enhanced chondrogenic differentiation of human stromal cells than collagen bioinks [97]. At present, several techniques are being used to treat cartilage defects and these include autologous chondrocyte implantation and matrix-induced autologous chondrocyte implantation [100,101].…”
Section: Decellularized Ecm As Bioinkmentioning
confidence: 99%